Efeito do tipo antidepressivo do disseleneto de difenila em um modelo de depressão induzida por malation em ratos - Acker, Carmine Inês (2010)
Organophosphorus (OP), among them malathion, are responsible for most of the poisonings reported annually in Brazil. In addition to symptoms of cholinergic poisoning, the exposure to OP causes affective and cognitive disorders, which are not necessarily related to acetylcholinesterase (AChE) enzyme activity inhibition. One of these disorders is depression. Diphenyl diselenide [(PhSe)2] is an organoselenium compound that presents pharmacological effects, among them the antioxidant effect. Therefore, this study was designed to investigate a potential antidepressant-like effect of (PhSe)2 on a depression model induced by malathion in rats. The role of Na+K+ ATPase, AChE and monoamine oxidase (MAO) activities and oxidative stress was investigated in cerebral cortices of rats. Rats were exposed once a day for three consecutive days to malathion (50 mg/kg, intraperitoneal) and (PhSe)2 (50 mg/kg, oral). To investigate the antidepressant-like behavior rats were submitted to the forced swimming test (FST) and the open-field test (OFT). Thiobarbituric acid reactive species (TBARS) levels, enzymatic and non-enzymatic antioxidant defenses were carried out in cerebral cortices of rats. The results confirmed that malathion increased immobility time in the FST without altering the locomotor performance in the OFT. Treatment with (PhSe)2 ameliorated performance in the FST without altering the crossing numbers in the OFT. The inhibition of Na+K+ATPase activity caused by malathion was prevented by treatment with (PhSe)2. Exposure to malathion did not alter parameters of oxidative stress as well as AChE and MAO activities in cerebral cortex of rats. In conclusion, (PhSe)2 exerted antidepressant-like effect in rats exposed to malathion. Na+K+ ATPase activity is, at least in part, involved in (PhSe)2 antidepressant-like behavior.